HYDROGELOLOGICAL PECULIARITIES OF CALCULATION OF SCARPS AND SLOPES STABILITY WITHIN URBANIZED TERRITORIES - Koshliakov, O.; Dyniak, O.; Koshliakova, I.; Koshliakova, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
forecasting is a reliable calculation of the stability and an adequate interpretation of the results, depending on the choice of the calculation method. Different methods of calculation, different complexity of their implementation and uncertainty of the results aggravate the problem, especially with regard to groundwater levels fluctuations and their further influence on sustainability parameters. The existing methods for calculating scarps and slopes stability, in particular taking into account temporary changes of groundwater levels, are analyzed. This study proves that the further increase in the reliability and accuracy of the results of calculations primarily depends on the improvement of methods for determining the water-physical state of soils and hydrodynamic features of groundwater movement. The authors provide evidence of the necessity to take into account intensity value of infiltration recharge at the predictive assessment of groundwater level. The role of anthropogenic component of infiltration recharge due to losses from water communications, especially in local areas, is investigated, which in the future will be reflected in engineering measures justification.